Ion irradiation-induced foams in antimonide binary alloys: A combination of small energy bandgap with giant surface-to-bulk ratio - Raquel Giulian; Charles A. Bolzan; Josiane Bueno Salazar; Carlo Requi\~ao da Cunha (Energy Reports, 2020)
This is a short review about the ion irradiation-induced foams in antimonide films. III-V semiconductors like InSb and GaSb can be transformed into solid foams with nanometric dimensions upon irradiation with swift heavy ions, increasing significantly the effective surface area of the material. The giant surface-to-bulk ratio of solid nanofoams, combined with the small energy bandgap of antimonide binary compounds offer new possibilities for the development of electronic devices with improved energy efficiency. The characterization of antimonide nanofoams structure, composition and electronic properties is thus essential to fully exploit their promising technological advantages. Here we show that InSb and GaSb films deposited by magnetron sputtering on SiO2/Si substrates can be rendered porous upon irradiation with 17 MeV Au+7 ions, while no evidence of porosity was observed in AlSb films irradiated under similar conditions. InSb films initially amorphous, become polycrystalline with zincblende phase upon irradiation with fluence 2x1014 cm-2, at the same time as the accumulation of voids result in the complete transformation of the films from compact-continuous to foam-like structure. Single-crystalline InSb films can also be transformed into solid foams upon irradiation, however, the ion fluence required to attain similar levels of porosity (compared to amorphous InSb deposited by magnetron sputtering) is significantly higher. GaSb films, in a similar way, can also be transformed into solid foams upon irradiation, although, for GaSb films deposited by magnetron sputtering, the structure of the foams is amorphous with significant increase of oxide fraction upon irradiation. The ion irradiation effects on the electronic properties of single crystalline InSb films are also presented. We compare the ion irradiation effects in different antimonide binary compounds with results about their crystalline structure and morphology using X-ray diffraction analysis and scanning electron microscopy.
Keywords: 330; Antimonide films; Ion irradiation; XRD; SEM